Maintaining Financial Liquidity in the Enterprise as a Condition for the Continuation of its Activities on the Example of Zakłady Mięsne Henryk Kania S.A. - Kuciński, Andrzej (Journal of Finance and Financial Law, 2021)
In an environment of increased uncertainty, in which modern enterprises have to operate, maintaining financial liquidity is a priority. Having financial liquidity by the enterprise determines the continuity of operations and its development. In the article, on the basis of the case study of the company Zakłady Mięsne Henryk Kania S.A., the shaping of the company’s payment capacity in 2015–2019 was analyzed using the short-term and long-term approach in the assessment of financial liquidity. The shown example shows that problems related to maintaining liquidity in an enterprise may lead to the bankruptcy of the enterprise.